Korupsi di Balik Pendidikan : Ketika Harapan Terenggut oleh Ketamakan - Maya Riskawati; Melsani Rawambani; Nadhirah Syaharani; Zalfa Rona Syafaqoh; Zhillan Dhiyaul Haq; Dadi Mulyadi Nugraha (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Corruption in the education sector is a serious problem that harms the state and has a direct impact on the quality of education and the future of the younger generation. This article discusses various forms of corruption in education, ranging from misuse of procurement project budgets to misappropriation of education grants. The impact of this corruption is seen in poor education facilities, inequitable access, and declining quality of teaching and curriculum. Overcoming these problems requires transparency, strict supervision, character education, and active community involvement in monitoring. Only with collective efforts and shared commitment can corruption in education be eradicated, so that the hope of creating a smart and competitive generation is maintained.